2015
DOI: 10.1016/j.niox.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

MMP-9- and NMDA receptor-mediated mechanism of diabetic renovascular remodeling and kidney dysfunction: Hydrogen sulfide is a key modulator

Abstract: Previously we reported that matrix metalloproteinase-9 (MMP-9) plays an important role in extracellular matrix (ECM) remodeling in diabetic kidney. Induction of NMDA-R and dysregulation of connexins (Cxs) were also observed. We concluded that this was due to decreased H2S production by down regulation of CBS and CSE enzymes. However, the potential role of H2S to mitigate ECM dysregulation and renal dysfunction was not clearly understood. The present study was undertaken to determine whether H2S supplementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 62 publications
14
48
0
Order By: Relevance
“…H 2 S was able to alleviate diabetic nephropathy in part by attenuating matrix deposition and inflammation [180]. Similar to their study, we also reported that in genetic diabetic Akita mice, diminished tissue and plasma H 2 S content was associated with matrix deterioration and diminished renal function [56, 57]. Increased matrix metalloproteinse-9 (MMP-9) expression and activity was noticed in Akita diabetic kidney which was normalized by H 2 S supplementation.…”
Section: Other Metabolic Disorders: H2s Is a Modulator Of Renal Dysupporting
confidence: 55%
See 3 more Smart Citations
“…H 2 S was able to alleviate diabetic nephropathy in part by attenuating matrix deposition and inflammation [180]. Similar to their study, we also reported that in genetic diabetic Akita mice, diminished tissue and plasma H 2 S content was associated with matrix deterioration and diminished renal function [56, 57]. Increased matrix metalloproteinse-9 (MMP-9) expression and activity was noticed in Akita diabetic kidney which was normalized by H 2 S supplementation.…”
Section: Other Metabolic Disorders: H2s Is a Modulator Of Renal Dysupporting
confidence: 55%
“…Direct correlation of diminished H 2 S and increased Ang-II was established by the fact that H 2 S treatment partially normalized all the above three effectors / inducers of hypertension in diabetic kidney [180]. Although this study in particular did not measure proteinuria and kidney function per se, we reported improved kidney function in Akita kidney [57]. Another study reported diuretic effect of H 2 S in spontaneously hypertensive diabetic rats in addition to reduction of blood pressure, restoration of H 2 S and plasma sodium levels compared to non-H 2 S treated diabetic rats [182].…”
Section: Other Metabolic Disorders: H2s Is a Modulator Of Renal Dymentioning
confidence: 91%
See 2 more Smart Citations
“…In established diabetic kidney injury in the Akita mice with type 1 genetic diabetes, Kundu et al have employed multiple mutually confirmatory approaches, including renal resistive index, to show a decrease in renal cortical blood flow that was associated with reduced vascular density; these changes were improved by the administration of NaHS (46).…”
Section: Diabetic Kidney Diseasementioning
confidence: 99%